1997
DOI: 10.1136/jnnp.63.4.477
|View full text |Cite
|
Sign up to set email alerts
|

Proton MRS and quantitative MRI assessment of the short term neurological response to antiretroviral therapy in AIDS

Abstract: Objective-To investigate MRI and proton spectroscopy changes in five patients with HIV associated dementia complex (HADC) treated with antiretroviral therapy. Methods-Three markers were evaluated: (1) CSF/intracranial volume ratio; (2) T2 weighted signal ratio between parietooccipital white and subcortical grey matter; and (3) metabolite ratios from long echo time (TE=135 ms) single voxel proton spectra of parieto-occipital white matter. Results-Spectroscopic changes indicated initial increases in N-acetyl/(N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…The finding of no change in Cho or Cr at short TE and yet significant change in Cho/Cr at long TE may reflect such a process. 7 No significant difference was found between the mean mI levels of the patient and control groups. However, a nonsignificant trend towards higher mI level (approximately 50%) was present in the patient group (as illustrated by the prominent resonance at 3.5 ppm in fig 1C) accompanied by a higher (20%) standard deviation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The finding of no change in Cho or Cr at short TE and yet significant change in Cho/Cr at long TE may reflect such a process. 7 No significant difference was found between the mean mI levels of the patient and control groups. However, a nonsignificant trend towards higher mI level (approximately 50%) was present in the patient group (as illustrated by the prominent resonance at 3.5 ppm in fig 1C) accompanied by a higher (20%) standard deviation.…”
Section: Discussionmentioning
confidence: 81%
“…It is thought that reduced neuronal density/death can be inferred from reduction in NAA obtained at short TE and possible reversible neuronal dysfunction can be implicated when NAA signal (and hence NAA/Cho or NAA/Cr ratios) is reduced at long TE. 7 Assuming equivalent neuronal development, the significantly lower short echo time NAA signal within the gluten ataxia group is suggestive of neuronal loss. It is possible that the results are indicative of cell dysfunction as well as neuronal loss since it has been shown that a strict gluten free diet can lead to improvement of the ataxia in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have suggested that NAA, the major constituent of the N-acetyl group resonance at long echo time (TE), is localized exclusively in neurons and their processes throughout the CNS [59][60][61]. In vivo cerebral NAA determined using H-MRS has been shown to correlate with histologic neuronal density in a variety of animal models [62]. It is also used as a surrogate neuronal marker for the assessment of neuroprotective therapeutic compounds/ strategies in humans [63].…”
Section: Brain Mr Spectroscopy In Dpnmentioning
confidence: 99%
“…As with imaging, spectra acquired at short TE and long TR are proton density-weighted and thus reflect metabolite concentration, whereas spectra acquired at long TE are T2-weighted, influenced by both concentration and individual metabolite T2. 19 In terms of the results of this study, the former implies no change in creatine concentration, whereas the latter implies no change in molecular environment (as this influences the metabolite's T2) within the cohort's frontal lobe white matter following dietary creatine augmentation. Accordingly, the results of this study (particularly those obtained at short TE) appear to contradict the findings of Dechent et al, 20 who report regional changes in the increase of the creatine pool over several weeks using a similar short echo time spectroscopic acquisition protocol at 2.0 T. The authors detail increases in creatine within deep gray matter (thalamus), cortical gray matter, deep white matter (parieto-occipital), and central cerebellum (P , 0.05).…”
Section: Discussionmentioning
confidence: 94%